The association of haemophilic arthropathy with Health‐Related Quality of Life: a post hoc analysis. (26th October 2016) - Fischer, K.; de Kleijn, P.; Negrier, C.; Mauser‐Bunschoten, E. P.; van der Valk, P. R.; van Galen, K. P. M.; Willemze, A.; Schutgens, R.
Abstract : Background: The aim of replacement therapy in haemophilia is to improve Health‐Related Quality of Life (HRQoL) by preventing bleeding and arthropathy. However, the association of arthropathy with HRQoL is unknown. Aim: To explore the association of haemophilic arthropathy with HRQoL. Methods: A post hoc analysis on patients with severe/moderate haemophilia with SF36 questionnaire (SF36) and X‐rays of ankles, knees and elbows made within 2.5‐years. The SF36 scores of 'physical functioning' (SF36‐PF, range 0–100, optimum 100) and Utility (SF6D‐Utility, range 0–1, optimum 1) and radiological Pettersson scores (PS, range 0–78, optimum 0) were calculated. The association of PS with reduced SF6D‐Utility and SF36‐PF (<age‐specific normal values) was analysed using ROC analyses and multivariable logistic regression. Results: Overall, 176 assessments were analysed: 130 from the Van Creveldkliniek and 46 from a French multicenter study. Most patients had severe haemophilia (89.9%), evaluated at 26.6 years, and with a range 15.7–65.8. Overall PS median (interquartile range) was 16 (7–34), SF6D‐Utility was 0.76 (0.64–0.86) and SF36‐PF was 85 (60–95). Receiver operating curve analysis identified a threshold PS of 21 points for both SF6D‐Utility (AUC 0.65) and SF36‐PF (AUC 0.76). In patients with PS > 21 points, the risk of reduced SF6D‐Utility was stable (OR 4.16; 95% CI: 2.03–8.51) but SF36‐PF continued to decrease: compared to lowest PS, OR for reduced SF36‐PF was 5.69 (95% CI: 1.62–20.06) for PS 22–39 and 25.15 (95% CI: 6.53–96.81) for PS 40–78. Conclusion: Health‐Related Quality of Life only showed a significant deterioration in patients with a Pettersson score of >21 points. This suggests that HRQoL is relatively insensitive to early joint changes.